ALGEBRA 1

posted by .

Lesson 3 Assignment .Explain the differences between solving these two equations: By steps
log3(x - 1) = 4
AND
log3(x - 1) = log3^4

  • ALGEBRA 1 -

    This is about the 4th time I have seen this question in the last couple of days

    http://www.jiskha.com/display.cgi?id=1297173059

    BTW, the way you typed it, they are the same equation.
    Both have the same solution.

  • ALGEBRA 1 -

    Log(3x+8)=1+log(x-7)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    (I have two questions) 1. Solve for x without a calculator: log3(x^2)=2log3(4)-4log3(5) This is what I have so far: 2log3(x)=log3(4^2)-log3(5^4) 2log3(x)=log3(16/625) ...and now I'm stuck. 2. Simplify: 2log4(9)-2log3 <--how do you …
  2. Precalculus

    Please help me with these questions ASAP!! Suppose that f(x)=log3(x-1) a)If f(6)=1.4 and f(8)=1.7,then evaluate log3(35) and log3(7/5). b)If f(3)=0.6, find log9(2).
  3. Andy

    Name: Lesson 3 Assignment.Instructions Explain the differences between solving these two equations: •log3(x - 1) = 4 and log3(x - 1) = log34. I think it has to do with the formulas
  4. Algebra 1

    Explain the differences between solving these two equations: •log3(x - 1) = 4 AND log3(x - 1) = log34 I think it has to deal with the formulas?
  5. Algebra 1

    Explain the differences between solving these two equations: Brake down the steps. log3(x - 1) = 4 and log3(x - 1) = log34 )
  6. Algebra 1

    Lesson 3 Assignment .Explain the differences between solving these two equations: By steps log3(x - 1) = 4 AND log3(x - 1) = log3^4
  7. Math

    Solve the logarithmic equation. Express your solutions in exact form only. Please show all of your work. log3(x+2) + log3(x+8) – 2 = log3(x+3)
  8. math

    Solve for x in the following equations. (4 marks) log3(x - 5) + log3(x + 3) = 2 <--- both log3.. 3 is subscript log7x + log7(x - 1) = log72x <--- all log7.. 7 is subscript.
  9. Pre-calculus

    Hi i need to find x in 9^(2x-6)=6^(8x-5) So what i did was: 3^(4x-12)=6^(8x-5) log3(3)^(4x-12)=log3(6)^(8x-5) 4x-12=(8x-5)log3(6) now i'm stuck. and i actually feel that the whole thing is wrong. help, pls
  10. Math

    Given that x=log3^5 and y=log3^2, rewrite log3^60 in terms of x and y.

More Similar Questions